Monolithic fabrication of nano-to-millimeter scale integrated transistors based on transparent and flexible silicon nanonets. Issue 2 (18th June 2019) - Nguyen, Thi Thu Thuy; Cazimajou, Thibauld; Legallais, Maxime; Arjmand, Tabassom; Nguyen, Viet Huong; Mouis, Mireille; Salem, Bassem; Robin, Eric; Ternon, C
Abstract: In this paper, silicon nanonets (SiNNs), a synonym of random networks of silicon nanowires (SiNWs), are demonstrated as a potential alternative to replace amorphous silicon (a-Si) or organic materials in flexible and large-area electronics. We first report the low temperature and monolithic integration of SiNW-based field-effect transistors (FETs) with a channel length varying from a micro-to-millimeter scale. For a channel as long as 1000 μ m, the current has to flow through a succession of at least a hundred SiNWs and as many SiNW–SiNW junctions. Despite this substantial related number of resistances in series, devices exhibit outstanding performances: a high drain current up to 10 −7 A, an I On / I Off ratio as large as 10 5 and a better mobility compared to a-Si and organic materials. Furthermore, such 1000 μ m long channel FETs exhibit better subthreshold slope and lower device-to-device variability compared to shorter channel ones (50–200 μ m). Good electrical stability is also observed after 4 months of exposure in air. In addition to these excellent features as a very long channel of transistors, silicon nanonets show good optical transparency and mechanical flexibility. These reported works make SiNNs a promising material for flexible and large-area electronics.